The fact that Salaf were keen to get to the meaning of the "two Shahadahs", the study discusses it's effect on the unity of Muslims.: عناية السلف بتأصيل مفهوم الشهادتين وأثره في وحدة الأمة - Shamsud Din, Dr. Abdur Rahman; Mian Jan, Dr. Ibrahim; Zeeshan, Dr. (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Subject of the Study: The fact that Salaf were keen to get to the meaning of the "two Shahadahs", the study discusses it's effect on the unity of Muslims. Methodology of the Research: The approach taken is inductive and descriptive. Main topics of the Research: The Research is composed of an Introduction, a preface, four chapters and an ending. Introduction: It is composed of Introductory words, essentials of the Study, Research plan and the Methodology of the Research. Preface contains: Definitions of the words composing the Research. First Chapter: Sahabah's passion to understand the meaning of "two Shahadahs". Second Chapter: The care "Tabieen" with which they approached to enhance their understanding of the "two shahadah". Third Chapter: The Patience with which the 'Four Imams' used to prioritize 'Shahadah' in order to understand meaning of "two Shahadahs". Fourth Chapter: The Utilization of the meaning of "two Shahdahs" and it's impact over the oneness and unity of the Muslim Ummah. Conclusion: It is composed of the extracted content from the Research.